Express: Learning new words via reading: the influence of emotional narrative context on learning novel adjectives - Dong, Y; Mak, MH; Hepach, R; Nation, K (SAGE Publications, 2024)
People learn new words in narrative contexts, but little is known about how the emotional valence of the narrative influences word learning. In a pre-registered experiment, seventy-six English-speaking adults read 30 novel adjectives embedded in 60 short narratives (20 positive, 20 negative, and 20 neutral valence). Both immediately after and 24 hours later, participants completed a series of post-tests including speeded recognition, sentence completion, meaning generation, and valence judgment. Results showed that participants learned both the novel word form and its meaning. Compared to novel words experienced in the neutral contexts, those read in the emotional contexts (both positive and negative) showed better learning of orthographic form in the immediate post-test, but only those read in the negative context were recognised with greater accuracy in the delayed post-test. Furthermore, the valence of the context was reflected in the word meanings participants generated for each novel word, suggesting that word valence can be inferred from the valence of the contexts. Results from sentence completion and valence judgment were mixed, depending on the task demands. These findings are discussed with reference to theories of affective embodiment and the implications for learning abstract words are considered.